Small Bowel Intussusception that was Needed Explorative Laparotomy because of Hypovolemic Shock - Ikwan Chang; Do Kyun Kim; Jea Yeon Choi; Dongbum Suh; Jae Yun Jung; Young Ho Kwak (Pediatric Emergency Medicine Journal, 2014)
Intussusception is the most common cause of gastrointestinal obstruction in children, which occurs most commonly in children aged between 3 and 12 months. Small bowel intussusception is uncommon in children compared to adults, and is not reduced by air reduction, unlike illeocecal intussusception. During the post-enema reduction period, patients could experience a delayed complication of hypovolemic shock. We report a case of small bowel intussusception that required explorative laparotomy due to hypovolemic shock. The patient was a 5 month-old female infant, who was diagnosed with small bowel intussusception and small bowel obstruction by sonography after a second air enema reduction. While observing her symptom, the patient's vital sign was becoming increasingly unstable. The patient received a large amount of fluid and inotropics. After a diagnostic computed tomography (CT) scan, the patient underwent explorative laparotomy to rule out bowel ischemia or necrosis. However, the patient's bowel was clear without minimal laceration on the surface of the bowel. After the operation, the patient recovered spontaneously. We suspect the patient's symptom and sign were caused by hypovolemia due to prolonged bowel ischemia and obstruction. Furthermore, resolving hypovolemic shock was caused by small bowel intussusception self-reduction. When pediatric physician is faced with small bowel intussusception in pediatric patients, they should provide adequate fluid supply and management along patient's state.